Recuperação avançada de petróleo através da injeção de soluções químicas aquosas ASP (álcali, surfactante, polímero) - Ruiz, Cindy Pamela Aguirre (2017)
Chemical oil recovery methods have proved to be successful for several cases as they allow to produce additional volumes of oil, although, economical profit should follow up such effectivity considering that developing such type of projects depend on such profits. Oil recovery methods are usually used after conventional methods such water flooding, as in some regions of northeastern Brazil. This work aimed to simulate and analyze the injection of aqueous chemical solutions (polymer, alkali and surfactant) within a reservoir portion that possess similar characteristics to those found in north eastern Brazil by using the Computer Modelling Group (CMG) computational tools. The analysis included both production volumes and a simple economic criterion such as NPV (Net Pay Volume). The methodology of this work included polymer, alkali and surfactant being injected within the reservoir in both separate and combined fashions, from the beginning of the reservoir´s productive life and after a water flooding process (when water cut reached a 90% value). Likewise, three different values of the international oil barrel´s price were considered in order to use the NPV criterion, aiming to use injection rates that would bring the higher profits. Results showed that the injection of aqueous chemical solutions, in terms of oil production and compared to water flooding, can be superior depending on operational parameters such as the type of product to be used, injection rates and the moment at which the oil recovery process starts during the reservoir´s productive life. The effectivity of oil recovery by injecting polymer was based on the increase of the aqueous solution´s viscosity and the pressure it provided to the reservoir. When it came to surfactant and alkali, their effectiveness depended on the reduction of the interfacial tension between oil and water phases, which allowed the reduction of the residual saturation of oil that turned into additional volumes of produced oil. According to the results obtained through the NPV criterion, additional volumes of produced oil did not necessarily translate into higher profits, and that the moment at which the chemical oil recovery method started had significant influenced the economic results. ASP combination stood up as the most favorable in terms of oil production and NPV.